Analisis Kesalahan Penggunaan kata keterangan 再(zài) dan 又(yòu) Dalam Bahasa Mandarin Pada Siswa Kelas VIII SMP Swasta Makassar - Andara, Givha Tri; Anwar, Muh; Azizah, Mir'ah (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2024)
This research is a qualitative descriptive study aimed at obtaining data on the level of errorsin the use of adverbs 再 (zài) and 又 (yòu) in Mandarin for Grade VIII students of SMPFrater Makassar. The population in this study were students of class VIII SMP FraterMakassar with a total of 27 students as well as research samples using the total sampletechnique. The research data was obtained by giving an error test using the adverbs 再 (zài)and 又 (yòu) consisting of True False, Filling, and Essay questions. The results showed thatthere were 124 errors in using the adverb 再 (zài) with 46.62% belonging to the less categoryand 142 errors in using the adverb 又 (yòu) with 53.38% belonging to the less category.Total errors There are 266 errors in the use of adverbs 再 (zài) and 又 (yòu).Keyword: Adverbs errors analysis 再 (zài) and 又 (yòu)